Evaluation of blood ethyl alcohol levels in the emergency service: the case of Şırnak province - Tahiroğlu, Veysel; İbrahimoğlu, Suna (My University, 2022)
T is known that drinking and driving is an important factor causing traffic accidents and this situation affects every part of the society. The data for which ethyl alcohol was requested from the şırnak state hospital automation system between 01/01/2020 and 01/07/2022 will be analyzed statistically. Demographic characteristics and ethyl alcohol results of patients admitted to the emergency department were obtained from the hospital information management system. 90.8% of the 306 requests are male and 9.2% are female. 50.7% of the requests are from young people between the ages of 18–29 and 5.9% are under the age of 18. When the cases were evaluated according to age, traffic accidents took first place among individuals between the ages of 18-29. In the evaluation of the cases according to gender, traffic accidents were found to be higher in males, and we found it statistically significant (p=0.016). When the cases were evaluated according to their ethyl alcohol levels, it was seen that 284 out of 306 people were below 50 ml/dL. It was determined that 191 people applied as a result of a traffic accident, but they were not alcoholics, and it was found to be statistically significant (P<0.001). It is important that the study has the first remarkable findings for the province of Şırnak. We tried to make predictions by looking at the data we obtained from this study. In this study, the majority of which are traffic accident claims, young adults and men are in the majority. However, it is noteworthy that traffic accidents do not occur due to alcohol, but traffic rules are not followed.
Keywords: Acil Tıp; Madde Bağımlılığı